Customer satisfaction towards online shopping in apparel industry / Nurul Niezar Norfaezar - Norfaezar, Nurul Niezar (Faculty of Business and Management, 2019)
The purpose of this research is to study the customer satisfaction towards online shopping in apparel industry. The goal of this study is to see the most factors that influence customer satisfaction towards online shopping in apparel industry. This research study is to examine the factors that influence the relationship between independent variable which include security and privacy, customer loyalty, service quality, convenience and dependent variable which is customer satisfaction. The questionnaires were distributed traditionally to the respondents which is UiTM Malacca Kampus Bandaraya student. The researcher used computer software which is Statistical programme for Social Sciences (SPSS) in analysing the data that been collected from the respondent. The data analysis was obtain in order to accomplish the objective of the research study which is to determine the relationship between security and privacy, customer loyalty, service quality and convenience with customer satisfaction. Besides that, it is also to identify the most impactful factor that influences customer satisfaction toward online shopping in apparel industry. Last but not least, the researcher hopes that this study will help online retailer to aware to the factor that influences the customer satisfaction in online shopping in apparel industry.